Performance of probiotic bacillus subtilis G1 as A dietary supplement for hemibagrus nemurus valenciennes fingerlings - Ahmad Affandi, Farhana (2014)
A study was carried out to investigate the probiotic activity of Bacillus subtilis G1 isolated from fermented pickles on Hemibagrus nemurus fingerlings at Universiti Putra Malaysia. Hemibagrus nemurus is a highly price fish that is commercially cultured in Southeast Asia for its excellent taste. However, H. nemurus is a slowgrowing fish that take almost a year to reach marketable price. Large-scales aquaculture of this fish has exposed the fish to a stressful condition such as diseases. Aeromonas hydrophila is known to be the famous bacterial infections in Bagridae catfishes. Growth hormones and antibiotics have been used for a long time in aquaculture to increase production and to prevent diseases. However, these substances have caused many problems. Therefore, probiotics are used as an alternative method for sustainable aquaculture. This probiotic was mixed in feed at doses of 0 (C, control), 109 (T1), 107 (T2) and 105 (T3) cfu g-1 and administrated to H. nemurus fingerlings for nine weeks. Results showed that H. nemurus fed with diet containing 107 cfu g-1 of B. subtilis G1 had significantly higher weight gain, total length and specific growth rate with 248.69 ± 3.31%, 13.65 ± 0.09 cm and 1.98 ± 0.09% respectively, and better protein efficiency ratio and food conversion ratio with 19.71 ± 0.33 and 1.68 ± 0.03 respectively, than those fed with the control, 105, and 109 cfu g-1 diets. Total protein gain of the body fish fed probiotic diets also increases with the increasing weight gain. This probiotic was also found to improve the water quality by lowering the NH3-N concentration.The haematological parameters such red blood cells, haemoglobin, haematocrit and mean corpuscular haemoglobin concentration, in the fish fed probiotic diets was higher compared to the control. Inhibitory activity of the probiotic B. subtilis G1 against fish pathogens such as Aeromonas hydrophila and Streptococcus agalactiae was evaluated by well diffusion agar method. Inhibition zone measured showed strong inhibitory activity against A.hydrophila and S. agalactiae with 16.13 ± 0.91 mm and 17.5 ± 1.84 mm respectively. Later, H. nemurus of all groups were fed with their respective diets for three weeks and then were challenged with 106 cfu ml-1 of A. hydrophila (0.1 ml) by intraperitoneal injection. After 14 days, the cumulative mortality of H. nemurus were significantly lower in the group T1 with 30 ± 5.8% as compared to the T2 (36.7 ± 3.3%), T3 (46.7 ± 3.3%) and C (56.7 ± 3.3%) groups. These findings proved that supplementation of B. subtilis G1 in the diet at 109 cfu g-1 can improve growth and disease resistance in H. nemurus fingerlings.